Regulation of a spindle positioning factor at kinetochores by SUMO-targeted ubiquitin ligases - Schweiggert, Jörg; Stevermann, Lea; Panigada, Davide; Kammerer, Daniel; Liakopoulos, Dimitris (Developmental cell, 2016)
Correct function of the mitotic spindle requires balanced interplay of kinetochore and astral microtubules that mediate chromosome segregation and spindle positioning, respectively. Errors therein can cause severe defects ranging from aneuploidy to developmental disorders. Here, we describe a protein degradation pathway that functionally links astral microtubules to kinetochores via regulation of a microtubule-associated factor. We show that the yeast spindle positioning protein Kar9 localizes not only to astral but also to kinetochore microtubules, where it becomes targeted for proteasomal degradation by the SUMO-targeted ubiquitin ligases (STUbLs) Slx5-Slx8.